Development of microsatellite markers using next-generation sequencing for the fish Colossoma macropomum - Ariede, Raquel B. [UNESP]; Freitas, Milena V. [UNESP]; Hata, Milene E. [UNESP]; Matrochirico-Filho, Vito A. [UNESP]; Utsunomia, Ricardo [UNESP]; Mendonça, Fernando F.; Foresti, Fausto [UNESP]; Porto-Foresti, Fábio [UNESP]; Hashimoto, Diogo T. [UNESP] (Springer Nature, 2018)
Tambaqui (Colossoma macropomum) is a fish species from the Amazon and Orinoco Rivers, with favorable characteristics to the cultivation system and great market acceptance in South America. However, the construction of a genetic map for the genetic improvement of this species is limited by the low number of molecular markers currently described. Thus, this study aimed to validate gene-associated and anonymous (non-genic) microsatellites obtained by next generation sequencing (RNA-seq and whole genome shotgun—WGS, respectively), for future construction of a genetic map and search for quantitative trait loci (QTL) in this species. In the RNA-seq data, the observed and expected heterozygosity (Ho and He) ranged from 0.09 to 0.73, and 0.09 to 0.85, respectively. In the WGS data, Ho and He ranged from 0.33 to 0.95, and 0.28 to 0.92, respectively. In general, the evaluation of 200 markers resulted in 45 polymorphic loci, of which 14 were gene-associated (RNA-Seq) and 31 were anonymous (WGS). Moreover, some markers were related to genes of the immune system, biological regulation/control and biogenesis. This study contributes to increase the number of molecular markers available for genetic studies in C. macropomum, which will allow the development of breeding programs assisted by molecular markers.
Keywords: Aquaculture; NGS; SSR gene-associated; Tambaqui